The role of cross sectional echocardiography and pulsed Doppler ultrasound in the management of neonates in whom congenital heart disease is suspected. A prospective study. Issue 1 (July 1986) - Leung, M P; Mok, C K; Lau, K C; Lo, R; Yeung, C Y
Abstract : The application of cross sectional echocardiography and pulsed Doppler ultrasound to the management of symptomatic neonates with suspected congenital heart disease was studied in 96 consecutive cases. The ability of echocardiography to establish a complete and accurate diagnosis and a correct management plan was evaluated. Sequential segmental analysis of data from cardiac catheterisation and necropsy identified 536 cardiovascular anomalies. Of the 536 anomalies 512 were correctly diagnosed by echocardiography (sensitivity 95.5%). Seven false positive echocardiographic diagnoses were made (specificity 98.6%). Nearly all the missing diagnoses and all the false positive diagnoses made by echocardiography were extracardiac vascular anomalies. Normal cardiovascular anatomy was at all times correctly identified by echocardiography. In 12 babies (12.5%) a management plan could not be established because of inconclusive echocardiographic findings. Of the 84 proposed plans based on the echocardiographic findings, eight were found to be inappropriate after catheterisation. Thus, 76 babies (79.2%) could have been correctly managed without cardiac catheterisation. The combination of cross sectional echocardiography and pulsed Doppler ultrasound not only allows diagnosis of congenital cardiac anomalies in most neonates but can facilitate appropriate clinical management. Only a minority of neonates with suspected congenital heart disease require cardiac catheterisation and angiography.